Acoustic Textiles - Padhye, Rajiv; Nayak, Rajkishore (Textile Science and Clothing Technology, 2016)
This book highlights the manufacturing and applications of acoustic textiles in various industries. It also includes examples from different industries in which acoustic textiles can be used to absorb noise and help reduce the impact of noise at the workplace. Given the importance of noise reduction in the working environment in several industries, the book offers a valuable guide for companies, educators and researchers involved with acoustic materials.